The Prolidase Activity, Oxidative Stress, and Nitric Oxide Levels of Bladder Tissues with or Without Tumor in Patients with Bladder Cancer - Gecit, Ilhan; Eryilmaz, Recep; Kavak, Servet; Meral, Ismail; Demir, Halit; Pirincci, Necip; Taken, Kerem (Springer, 2017)
This study was designed to evaluate the malondialdehyde (MDA), glutathione (GSH) and nitric oxide (NO) levels, and also prolidase, glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) enzyme activities in malignant and benign cancers of bladder tissue. A total of 59 patients admitted to our clinic due to microscopic or macroscopic haematuria, were prospectively included in the study. Because of some reasons (no request to participate in the study, the inability to reach, other malignancies, alcohol consumption, metabolic disease), eight patients were excluded from study. Of the 51 patients, 25 were bladder tumor patients, and 26 were patients without cancers. The bladder tissue samples were obtained from all patients under anesthesia (spinal, epidural or general) for the measurement of MDA, GSH and NO levels, and prolidase, GSH-Px and SOD enzyme activities. Among the patients with bladder cancers, 7 patients were females and 18 patients were males, with an average age of 68.4 +/- 2.49. Among patients without tumors, 6 patients were females and 20 patients were males, with an average age of 58 +/- 2.05. In patients with bladder tumors, the oxidants (MDA, NO, prolidase) were higher, and the antioxidants (SOD, GSH, GSH-Px) were lower than those in patients without tumors. It was concluded that the oxygen free radicals play a role in the etiology of bladder cancers similar to many other tumors and inflammatory conditions. Therefore, we assume that antioxidants may provide benefits in the prevention and treatment of bladder cancer.
Keywords: Cancer; Bladder; Status antioxidants; Superoxide dismutase; Nitric oxide; Oxidative stress